THE EFFECTIVENESS OF THE LEARNING INSTRUCTIONAL MATERIALS MONITORING INFORMATION SYSTEM (SIMOP) AS A DECISION-MAKING INSTRUMENT WITHIN THE DEPARTMENT OF EDUCATION OF TAKALAR REGENCY - Nurdin, Muhammad; Muhammad Yahya; Hasanah Nur (Jurnal Vokasi Keteknikan, 2026)
Digital transformation in educational governance necessitates monitoring systems that are effective, efficient, and accountable. This study aims to develop and evaluate the quality of a web-based Learning Tools Monitoring Information System (SIMOP) in Takalar Regency. The research employs a Research and Development (R&D) approach integrating the ADDIE, Prototype, Agile, and Waterfall models. System quality evaluation refers to the ISO/IEC 25010 standard established by the International Organization for Standardization (ISO). Data were collected through observations, interviews, and questionnaires administered to teachers, school principals, supervisors, and officials of the Department of Education. The results indicate that SIMOP falls within the “highly valid” category based on assessments of functional suitability, reliability, usability, portability, and security. The level of practicality reached 89.99%, while effectiveness achieved 91.82%. Teachers’ readiness was categorized as “highly ready” (90.35%), whereas responses from school principals and the Department of Education were 90.93% and 95%, respectively. The system has been proven to enhance efficiency, transparency, and accountability in monitoring instructional materials.